Building Materials Management Information System using the Web-Based Perpetual Inventory System - Febryantahanuji Febryantahanuji; Haryo Kusumo (Brilliant International Journal Of Management And Tourism, 2022)
Company that is engaged in construction contractors, has a project warehouse that is located moving around following the project being worked on. The problem faced is that the recording of material inventory is still done manually using a stock control card, then after that it is recorded it is entered into Microsoft Excel, it causes a long recording of material data stock because it has to open the parts one by one first for report generation. The research objective is to produce a system that can speed up the process of recording stock of building materials in the construction project warehouse, and can produce various material inventory reports that can control the availability of material inventory in the project warehouse. The method used is the Perpetual Inventory System, namely material management is carried out by controlling the stock of material inventory directly per periodic and continuously updating the stock every time material enters or exits. With this system, it will help the administration, foremen and project leaders to speed up various reports on stock control of material supplies that are fast, accurate and thorough and can improve the performance of officers in presenting reports.